Mast cells and basophils: trojan horses of conventional lin- stem/progenitor cell isolates - Heneberg, Petr (Current pharmaceutical design, 2011)
Cancer microenvironment is increasingly recognized as an important factor affecting cancer onset and progression. Since Wirchow reported in 1863 that tumors contain inflammatory cells, the field shifted significantly forward, and immune cells residing in tumors appear to be attractive targets of cancer therapies. For some methods, such as stem/progenitor cell isolation from both cancer and healthy tissues, removal of contaminating immune cells is crucial to achieve consistent, reproducible and accurate results. Despite current methods of lineage negative selection accounts for removal of over 99 % of immune cells from stem/progenitor cell isolates, the vast majority of lineage antibody cocktails retain basophils, dendritic cells, and mast cells. Here we discuss the ability of the most commonly used lineage markers to bind to the plasma membrane of mast cells and/or basophils, and suggest alternatives, which may be used for negative selection of these cellular populations. Both, mast cells and basophils, were shown to participate actively in cancer-associated angiogenesis, tissue remodeling and recruitment of other immune cell types, including eosinophils, B cells, memory T cells and Treg cells. In turn, tumor-derived peptides and chemotactic factors are known to recruit and activate mast cells in neoplasias, resulting in altered tumor progression. Repeated findings of CD34+ populations of mast cells and basophils further highlight necessity of their separation from stem/progenitor cell isolates in both, preclinical experiments and clinical praxis.
Keywords: antigeny povrchové; mastocyty; Animals; Cell Lineage; Mast Cells; Stem Cells; buněčný rodokmen; Neoplasms; nádory; Molecular Structure; lidé; Antineoplastic Agents; protinádorové látky; bibliometrie; kmenové buňky; databáze faktografické; Bibliometrics; molekulární struktura; bazofily; Basophils; Databases, Factual; zvířata; Antigens, Surface; Humans